Application of modified carbon fiber loaded lanthanum composite material as phosphorus adsorbent

Through the chemical adsorption and ion exchange technology of modified carbon fiber-loaded lanthanum composite materials, the problem of poor phosphorus removal in natural water bodies is solved, efficient phosphorus removal and resource recovery is achieved, and a low-cost, recyclable solution is provided. , suitable for long-term restoration of natural water bodies.

CN119258982AInactive Publication Date: 2025-01-07NANJING TECH UNIV

Patent Information

Application Number
CN202411325620.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional phosphorus removal technology is not effective in the restoration of natural water bodies, with high cost and high maintenance requirements. In addition, water bodies are easily contaminated again under the impact of external pollution, making it difficult to achieve long-term phosphorus removal effect.

Method used

Use modified carbon fiber-loaded lanthanum composite material as phosphorus adsorbent, and remove phosphorus from the water through chemical adsorption and ion exchange processes and realize resource recycling. The affinity of lanthanum and the high specific surface area and surface activity of carbon fiber are used to adhere to phosphorus and precipitation.

Benefits of technology

It realizes efficient removal and resource recycling of phosphorus in eutrophied water bodies. The material has high adsorption capacity, is not affected by other anions, is recycled and has a simple preparation process, is low cost, and is suitable for long-term repair of natural water bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258982A_ABST
    Figure CN119258982A_ABST
Patent Text Reader

Abstract

The invention discloses an application of a modified carbon fiber loaded lanthanum composite material as a phosphorus adsorbent, belongs to the field of ecological pollution control engineering, and particularly relates to a technology for phosphorus adsorption and resource utilization of an impregnation method modified carbon fiber loaded lanthanum composite material in eutrophicated water. The prepared carbon fiber loaded lanthanum composite material has the advantages of high phosphate adsorption capacity, no influence of other anions on the adsorption performance, recyclability, simple preparation process, low cost and the like, and has a wide application prospect in the aspect of treating eutrophic water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ecological pollution control engineering, and in particular relates to a technology for adsorbing and recycling phosphorus in eutrophic water bodies by using a lanthanum composite material modified by an impregnation method. Background Art

[0002] Phosphorus is one of the essential elements in nature for human life and production. It is extremely important for life activities and is an important nutrient for life on Earth. However, excessive phosphorus can cause eutrophication of water bodies and damage the balance of ecosystems such as lakes and reservoirs. Freshwater lakes are increasingly vulnerable to global changes such as climate change, as well as the pressure of increasing nutrient loads caused by human activities, threatening future water and food security.

[0003] In surface water, phosphorus concentration exceeding 0.05 mg / L will cause eutrophication of water bodies, and the use of phosphate fertilizers and the discharge of phosphorus-containing wastewater are one of the important causes of eutrophication of water bodies. When eutrophication is severe, "water blooms" and algal toxins are produced, which damage the utilization of water resources and bring serious adverse consequences to the lake water environment and ecosystem. Lakes and reservoirs are part of the hydrological cycle of their basins. Lakes continuously exchange fluxes with the atmosphere, groundwater and surface water. Lakes play an important role in the biogeochemical cycles of continental basins. There are two processes driving these biogeochemical cycles, especially the carbon, nitrogen and phosphorus cycles: primary production and the sedimentation of particulate matter. Therefore, the control of phosphorus in lakes is of great significance for the remediation of eutrophic water bodies.

[0004] Traditional phosphorus removal methods are mainly divided into biological phosphorus removal, ecological phosphorus removal and chemical phosphorus removal. In the sewage purification process, biological phosphorus removal is mainly achieved by anaerobic phosphorus release by microorganisms and aerobic excess phosphorus absorption, which is converted into polyphosphate in the cell body, thereby forming phosphorus-rich biological sludge, which is discharged from the system through precipitation to achieve phosphorus removal. Biological phosphorus removal involves a variety of influencing factors, such as dissolved oxygen (DO), temperature, biological oxygen demand (BOD), etc., which leads to extremely unstable treatment and recovery effects and large performance fluctuations. Ecological phosphorus removal is generally represented by ecological pond technology. By planting tall landscape vegetation, phosphorus in sewage is assimilated and absorbed into plant biomass to achieve phosphorus purification. This process requires timely harvesting and management of landscape vegetation, and the reasonable allocation of pioneer species needs to be considered to achieve seasonal rotation. In contrast, chemical phosphorus removal methods including chemical adsorption, chemical precipitation, ion exchange, etc. have become the preferred choice in water purification processes because of their easy operation and low cost. In addition, chemical phosphorus removal has the advantages of higher efficiency and more stable effect than biological phosphorus removal. When biological treatment fails to meet the standards, chemical enhanced phosphorus removal is usually used to deeply remove phosphorus from wastewater.

[0005] However, in the restoration of natural water bodies, traditional phosphorus removal technology solutions are greatly limited. First of all, biological ecological phosphorus removal must be achieved by transferring residual sludge or harvesting plants. Since phosphorus is a sedimentary element, phosphorus removal in natural water bodies must be achieved through dredging or timely harvesting of large aquatic vegetation, which requires high costs and maintenance. And if the external pollution is serious, the bottom mud in the water body will be polluted again in a short period of time. Therefore, the effect of dredging projects in most domestic lakes is usually short-lived, generally ranging from one month to one or two years. Excessive external pollution impact is not conducive to the recovery and growth of large aquatic vegetation, so the effect of ecological phosphorus removal is also very limited. Chemical phosphorus removal in natural water bodies generally achieves in-situ fixation of phosphorus by adding passivation materials to form stable compounds between phosphorus in water bodies and sediments, so as to limit the release of phosphorus in sediments to overlying water, thus becoming in-situ chemical passivation. Summary of the invention

[0006] In view of the above-mentioned technical problems, the present invention provides a natural water phosphorus adsorption technology, which is based on chemical adsorption phosphorus removal, using adsorbents (activated carbon fibers) to provide a large specific surface area and strong surface activity, and by loading metals (lanthanum) with phosphorus affinity on the adsorbent material, phosphorus is attached to the adsorbent surface, ion exchange or surface precipitation process is achieved, and phosphorus is removed from the water body. Through solid phase adsorption and desorption, phosphorus in eutrophic water bodies is removed and recycled.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] The invention discloses an application of a modified carbon fiber loaded lanthanum composite material as a phosphorus adsorbent.

[0009] In the above application: application of the composite material in adsorbing phosphorus in eutrophic water.

[0010] In the above application: The preparation method of the modified carbon fiber loaded lanthanum composite material is as follows: sodium hydroxide is added to the lanthanum nitrate solution and mixed to react, after precipitation occurs, ultrasound is performed and carbon fiber is added and ultrasound is performed again, and then the modified carbon fiber loaded lanthanum composite material is obtained after washing, drying and calcining in sequence.

[0011] In the preparation method of the above catalyst: the calcination temperature is 350-450°C, and the calcination time is 2-3h.

[0012] In the preparation method of the above catalyst: the modified carbon fiber loaded lanthanum composite material uses carbon fiber as a carrier, lanthanum as an active component, and the mass ratio of carbon fiber to lanthanum element is 1:5.

[0013] In some more specific technical solutions, the preparation method of the modified carbon fiber loaded lanthanum composite material comprises the following steps:

[0014] Step 1: dissolve an appropriate amount of lanthanum nitrate in pure water and dilute to a corresponding volume;

[0015] Step 2, adding sodium hydroxide and stirring with a magnetic stirrer until precipitation occurs to form a suspension;

[0016] Step 3, placing the suspension into an ultrasonic cleaning machine for ultrasonication to disperse the suspension;

[0017] Step 4, adding an appropriate amount of carbon fiber material and ultrasonicating again, and washing the carbon fiber material with water until it is neutral;

[0018] Step 5: After washing the material to neutrality, place it in an oven for drying, and calcine it in a muffle furnace for 2 hours. The calcined product is cooled to obtain a modified carbon fiber loaded lanthanum composite material.

[0019] Preferably, in step 1, 21.58 g of lanthanum nitrate hexahydrate is added and dissolved in 500 ml of pure water, and the lanthanum concentration is 0.1 mol / L.

[0020] Preferably, in the step 2, an appropriate amount of 0.1 mol / L sodium hydroxide solution is added and stirred continuously until precipitation occurs and the pH is adjusted to 10, and then stirring is continued until the suspension is evenly distributed in the beaker.

[0021] Preferably, in step three, the ultrasonic frequency is 100 Hz and the time is 10 min to disperse the suspension.

[0022] Preferably, in the step 4, the carbon fiber material is cut into pieces of 2-3 cm and 5 g, placed in a suspension, and ultrasonicated at a frequency of 100 Hz for 10 min.

[0023] Preferably, in step 5, the oven temperature is 80° C. and the drying time is 6 h; the muffle furnace temperature is 350-450° C. and the calcination time is 2-3 h.

[0024] Beneficial effects of the present invention:

[0025] 1. Carbon fiber is used as a carrier of composite materials, and the surface of the material has more adsorption active sites, thereby improving the adsorption performance; 2. Carbon fiber itself has adsorption properties for phosphorus, and after being modified by the impregnation method, the adsorption capacity increases;

[0026] 3. The prepared carbon fiber loaded lanthanum composite material has the advantages of high phosphate adsorption capacity, adsorption performance is not affected by other anions, recyclable, simple preparation process and low cost, and has broad application prospects in the treatment of eutrophic water bodies. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1is an X-ray diffraction (XRD) pattern of the modified carbon fiber loaded lanthanum composite material prepared by the present invention to phosphate;

[0028] Figure 2 Adsorption kinetics curve of the modified carbon fiber loaded lanthanum composite material prepared by the present invention;

[0029] Figure 3 The adsorption amount of phosphate by the modified carbon fiber loaded lanthanum composite material prepared by the present invention at different ion concentrations;

[0030] Figure 4 A schematic diagram of a simulated water flow device for a modified carbon fiber loaded lanthanum composite material prepared in the present invention;

[0031] Figure 5 The modified carbon fiber loaded lanthanum composite material prepared for the present invention is based on a simulated water flow device, and the adsorption effect on water samples from Chaohu Lake, Anhui Province in winter (January 2024) is studied.

[0032] Figure 6 The modified carbon fiber loaded lanthanum composite material prepared for the present invention is based on a simulated water flow device, and the adsorption effect on water samples from Chaohu Lake, Anhui in summer (July 2024) is studied.

[0033] Figure 7 This is the total phosphorus limit for lakes and reservoirs in the national "Surface Water Environmental Quality Standard GB3838-2022".

[0034] Figure 8 The modified carbon fiber loaded lanthanum composite material prepared by the present invention has the effect of adsorption and recovery of phosphorus after five cycles. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto:

[0036] The preparation method of the modified carbon fiber loaded lanthanum composite material is as follows:

[0037] Step 1: dissolve an appropriate amount of lanthanum nitrate in pure water and dilute to a corresponding volume;

[0038] Step 2, adding sodium hydroxide and stirring with a magnetic stirrer until precipitation occurs to form a suspension;

[0039] Step 3, placing the turbid liquid into an ultrasonic cleaning machine for ultrasonication to disperse the suspension;

[0040] Step 4, adding an appropriate amount of carbon fiber material and ultrasonicating again, and washing the carbon fiber material with water until it is neutral;

[0041] Step 5: After washing the material to neutrality, place it in an oven for drying, and calcine it at 400° C. for 2 hours. The calcined product is cooled to obtain a modified carbon fiber loaded lanthanum composite material.

[0042] In the step 1, 21.58 g of lanthanum nitrate hexahydrate was added and dissolved in 500 ml of pure water, and the lanthanum concentration was 0.1 mol / L.

[0043] In the second step, add an appropriate amount of 0.1 mol / L sodium hydroxide solution and stir continuously to adjust the pH to 10, and then continue stirring until the suspension is evenly distributed in the beaker.

[0044] Preferably, in the step 4, 5 g of carbon fiber material is cut into 2-3 cm, placed in the suspension, and ultrasonicated at a frequency of 100 Hz for 10 min.

[0045] Preferably, in step 5, the oven temperature is 80° C. and the drying time is 6 h; the muffle furnace temperature is 350-450° C. and the calcination time is 2-3 h.

[0046] Example 1: The modified carbon fiber loaded lanthanum composite material obtained in the above example is analyzed by X-ray diffractometer, and its XRD spectrum can be obtained as follows: Figure 1 As shown, the lanthanum hydroxide adsorbent generated by the reaction of lanthanum nitrate and sodium hydroxide exhibited diffraction peaks of 2θ values ​​at 15.6° and 27.1°, which are typical characteristics of lanthanum hydroxide.

[0047] Example 2: Accurately weigh 0.1g of modified carbon fiber loaded lanthanum composite material into a conical flask, add 100ml of 4mg / L phosphorus solution, stir and adsorb at 25°C, take out the supernatant at 20, 40, 60, 80, 100, and 120min, analyze the remaining phosphorus concentration in the sample by phosphomolybdenum blue colorimetry, calculate the adsorption amount, and use pseudo-first-order and pseudo-second-order kinetic models to fit the adsorption process. The supernatant was filtered through a 0.45μm PES syringe filter (MILLIPORE). The obtained solution was analyzed for phosphorus concentration using the ammonium molybdate method. In the experiment, 0.1mol / L sodium hydroxide and 0.1mol / L hydrochloric acid maintained the pH of the solution at 7.0±0.2. Figure 2 As shown in the figure, the adsorption of phosphorus by the modified carbon fiber loaded lanthanum composite material is a process of rapid adsorption and slow equilibrium. After 1h of reaction, the adsorption amount of phosphorus by the modified carbon fiber loaded lanthanum composite material reached 0.9mg / g, and then the adsorption amount increased slowly, reaching 1.0mg / g in 2h, reaching adsorption equilibrium. This shows that the modified carbon fiber loaded lanthanum composite material has a high adsorption efficiency.

[0048] Example 3: The anti-interference ability of the absorbent is of great significance to its application in practical water treatment. Cl-, SO2-4, NO-3, and CO2-3 are common anions. Given that they may compete with phosphate for active adsorption sites on carbon fiber composites, resulting in a decrease in the phosphate adsorption efficiency of biochar, batch adsorption experiments were conducted to evaluate the effects of different concentrations of competing anions and organic matter on phosphate removal performance.

[0049] In the experiment, 0.25g / L modified carbon fiber loaded lanthanum composite material was placed in 0.2mg-P / L phosphate solution, and different concentrations (0, 50, 100, 150, 200mg / L) and different types of competitive ions (Cl-, SO2-4, NO-3, CO2-3) were added to it. In the experiment, 0.1mol / L sodium hydroxide and 0.1mol / L hydrochloric acid maintained the pH of the solution at 7.0±0.2.

[0050] Depend on Figure 3 It can be seen that Cl- ions and NO-3 have no effect on the adsorption effect; SO2-4 ions and CO2-3 have a slight effect, and the adsorption amount will decrease slightly, but the removal efficiency can still be maintained above 95%. This shows that the modified carbon fiber loaded lanthanum composite material has excellent performance in the adsorption of phosphorus in the presence of competing ions.

[0051] Example 4: The flow characteristics of lakes are generally poor fluidity, low turbidity, high transparency, but the water flow is not easy to mix, and there will be uneven water quality distribution. In order to better simulate the flow of modified carbon fiber loaded lanthanum composite materials in water, a device is built such as Figure 4 As shown, the parts are: 1-water inlet tank, 2-peristaltic pump, 3-reaction tank, 4-water outlet tank. The hydraulic retention time of the device is 2h.

[0052] Samples were collected from Chaohu Lake, Anhui Province in winter (January 2024) and summer (July 2024). Figure 4 The experimental device was used. About 7L of Chaohu water sample was added to the water inlet tank 1 at room temperature. The flow rate of the peristaltic pump 2 was set to 2.5, and the hydraulic retention time was maintained at 2h. 1.0g of modified carbon fiber loaded lanthanum composite material was added to the reaction tank 3. 50ml of water sample from the water outlet tank 4 was collected every two hours to determine inorganic phosphorus and total phosphorus respectively. No treatment was done to the water samples during the experiment.

[0053] The experimental results are as follows Figure 5 , Figure 6 shown. Figure 5 This is a water sample from Chaohu Lake in winter (January 2024). It can be seen that the initial inorganic phosphorus concentration is 0.036 mg / L, the total phosphorus concentration is 0.058 mg / L, and the inorganic phosphorus accounts for 62%. Figure 7According to the total phosphorus standard for lakes and reservoirs in the national "Surface Water Environmental Quality Standard GB3838-2022", this lake belongs to Class IV surface water bodies. After adsorption by modified carbon fiber loaded lanthanum composite materials, the inorganic phosphorus and total phosphorus in the effluent can be reduced to 0.001 mg / L, reaching Class I surface water bodies.

[0054] Figure 6 This is a water sample from Chaohu Lake in summer (July 2024). It can be seen that the initial inorganic phosphorus concentration is 0.026 mg / L, the total phosphorus concentration is 0.036 mg / L, and the inorganic phosphorus accounts for 72%. Figure 7 According to the total phosphorus standard for lakes and reservoirs in the national "Surface Water Environmental Quality Standard GB3838-2022", the lake belongs to Class III surface water at this time. After adsorption by modified carbon fiber loaded lanthanum composite material, the inorganic phosphorus and total phosphorus in the effluent can be reduced to 0.001 mg / L, reaching the Class I surface water standard; at the same time, due to the vigorous growth of algae in the water body in summer, it has a certain impact on the adsorption effect and the determination of adsorption results. The results show that the inorganic phosphorus and total phosphorus can be reduced to 0.018 mg / L and 0.02 mg / L, which can meet the Class II surface water standard and below.

[0055] Therefore, the adsorption of modified carbon fiber loaded lanthanum composite materials has certain practical significance for the removal of phosphorus in eutrophic water bodies.

[0056] Example 5: Analyze the adsorption effect of the modified carbon fiber loaded lanthanum composite material on phosphorus by repeated use. During the analysis, take 100ml of 1mg / L phosphate solution and place it in a 150ml conical flask. At the same time, add 0.1g of the modified carbon fiber loaded lanthanum composite material. Place the conical flask in a 25℃ water bath constant temperature oscillator. After oscillating at 160rpm for 12h, test the phosphorus concentration of the supernatant to calculate the adsorption rate. Collect the used modified carbon fiber loaded lanthanum composite material, add 100ml of 0.75mol / L sodium hydroxide and 0.1mol / L sodium bicarbonate mixed solution, place it in a 25℃ water bath constant temperature oscillator, oscillate at 160rpm for 12h, remove the supernatant to determine the phosphorus concentration and calculate the desorption rate, and wash it with pure water 5 times. The obtained precipitate is dried at 100 degrees and used again to adsorb phosphorus, and the above adsorption process is repeated five times. The adsorption / desorption rate obtained from the five data is as follows Figure 8 As shown in the figure, it can be seen that after being recycled for 5 times, the modified carbon fiber loaded lanthanum composite material can still achieve a phosphorus adsorption rate of more than 80%, and a desorption rate of more than 60%, which has huge research and development potential for phosphorus recovery.

Claims

1. Application of a modified carbon fiber loaded lanthanum composite material as a phosphorus adsorbent.

2. The use according to claim 1, characterized in that: The composite material is used for adsorbing phosphorus in eutrophic water.

3. The use according to claim 1, characterized in that: The preparation method of the modified carbon fiber loaded lanthanum composite material is as follows: sodium hydroxide is added to a lanthanum nitrate solution and mixed to react, ultrasonication is performed after precipitation occurs, and carbon fiber is added and ultrasonication is performed again, and then washing, drying and calcining are performed in sequence to obtain the modified carbon fiber loaded lanthanum composite material.

4. The use according to claim 3, characterized in that: The calcination temperature is 350-450°C, and the calcination time is 2-3 hours.

5. The use according to claim 3, characterized in that: The modified carbon fiber loaded lanthanum composite material uses carbon fiber as a carrier and lanthanum as an active component, and the mass ratio of the carbon fiber to the lanthanum nitrate element is 1:2-5.

6. The use according to claim 3, characterized in that: The drying temperature is 70-80°C and the drying time is 5-6 hours.

Citation Information

Patent Citations

  • Phosphate removing agent prepared by loading lanthana on active carbon fibre substrate and preparation method thereof

    CN102008940A

  • Preparation method of active carbon fiber phosphorous removing agent carrying lanthanum hydroxide

    CN102247804A

  • Activated carbon fiber adsorbent loaded with lanthanum hydroxide and preparation method thereof

    CN102350306A

  • Phosphorus removal adsorbent for loading composite metal via active carbon fiber and preparation method of phosphorus removal adsorbent

    CN103203219A

Cited By

  • Multi-effect phosphorus removal and algae control device

    CN120081508A

  • Phosphorus-fixing lanthanum-based nano composite material as well as preparation method and application thereof

    CN121869308A